Pengaruh Rasio CAMEL dan Faktor Makroekonomi terhadap Kondisi Financial Distress pada Bank BUSN Non Devisa Tahun 2014-2019 - Wella Wahyu Qur'anna; Yuyun Isbanah (Jurnal Ilmu Manajemen, 2021)
The bank, as financial intermediaries, is institutions that collect funds from society and distribute those funds for credit and providing other banking services. So, banking health is essential to prevent banks from Financial distress that leads to bankruptcy. This study analyses the effect of the CAMEL ratio and macroeconomic factors to predict non-foreign exchange bank is in 2014-2019 Financial distress. The CAMEL ratio consists of Capital proxied by CAR (Capital Adequacy Ratio), Asset Quality proxied by NPL (Non-Performing Loan), Management proxied by BOPO (Operating Expense to Operations Income), Earning proxied by ROA (Return on Asset), Liquidity proxied by LDR (Loan to Deposit Ratio). Then, macroeconomic factors proxied by GDP (Gross Domestic Product) and Inflation. This study used 20 non-foreign exchange bank is in 2014-2019 as the sample was determined using purposive sampling, and the statistical methods used to analyze is logistic regression in SPSS 25. This study shows that CAR, NPL, BOPO, LDR, GDP and Inflation have no significant effect on the probability of a bank's financial distress. On the other hand, ROA has a significant effect on the probability of a bank's financial distress.